Metastatic rectal cancer in the ampulla of Vater: A unique case - Athina A. Samara; Ioanna‐Konstantina Sgantzou; Alexandros Diamantis; Alexandros Kokkalis; Konstantinos Tsapakidis; Maria Tolia; Gregory Christodoulidis; Christos Rountas; Dimitris Zacharoulis (Cancer Reports, 2022)
Abstract Background A metastatic lesion located in the ampulla of Vater is considered extremely rare, with only 32 cases reported globally. Case A 65‐year‐old patient was primarily diagnosed with a rectal adenocarcinoma. Twenty‐four months later as part of the oncological follow‐up, the patient was diagnosed with a single secondary tumor in the ampulla of Vater. After undergoing a pancreaticoduodenectomy (Whipple procedure), the patient experienced an uneventful recovery and received adjuvant chemotherapy. Sixteen months later the patient remained disease‐free. Conclusion To the best of our knowledge, the present case represents the first reported metastatic tumor in the ampulla of Vater, originating from a rectal adenocarcinoma. This case underlines the critical role of immunohistochemistry in arriving at a correct diagnosis in order to guide clinical decision‐making.